NONLINEAR ANALYSIS OF RENFORCED FIBROUS CONCRETE VIERENDEEL TRUSS (Journal of Engineering, 2008)
A Vierendeel truss is a hyper static frame composed of a series of rectangular or trapezoidal panels with out diagonal members. The end conections of all members are rigid and designed to take moment. In this work, the use of fiber reinforced concrete in construction of Vierendeel trusses with nonlinear material behavior is researched. The addition of randomly dispersed discrete steel fibers to concrete improves many engineering properties of the material such as fracture toughness, fatigue resistance, impact resistance and flexural strength. Several parameters that affected the behavior of the structure like fiber volume fraction, aspect ratio, and the position of the portion in structure that used fibrous concrete are studied. All these studies are hold out by developing aprogram, named (P3DNFEA).